Institutional and provider variations for mechanical thrombectomy in the treatment of acute ischemic stroke: a survey analysis. (13th February 2019) - Mehta, Tapan; Male, Shailesh; Quinn, Coridon; Kallmes, David F; Siddiqui, Adnan H; Turk, Aquilla; Grande, Andrew Walker; Tummala, Ramachandra Prasad; Jagadeesan, Bharathi Dasan
Abstract : Introduction: Stent retriever combined with aspiration, or the 'Solumbra technique', has recently emerged as one of the popular methods of mechanical thrombectomy (MT). However, the variations in understanding and implementation of the Solumbra technique have not been reported. Methods: An 18 part anonymous survey questionnaire was designed to extract information regarding technical variations of MT with a focus on the Solumbra technique. The survey link was posted on the Society of Neurointerventional Surgery (SNIS) website in 'SNIS connect'. Results: 80 responses were obtained over 4 weeks that were included in the final analysis. Direct aspiration without a balloon guide catheter (BGC) was the most favored technique among respondents (41.12%) followed by the Solumbra technique without a BGC (32.4%). Among those using the Solumbra technique, 77.6% reported that they wait between 2 and 5 min to allow clot engagement, 55.2% always remove the microcatheter before aspiration, and 69.1% commence aspiration through the intermediate catheter only when retrieving the stent retriever. Operators who infrequently used or did not use BGCs reported a higher incidence of >80% Thrombolysis in Cerebral Infarction 2b/3 annual recanalization rates (OR 8.85, 95% CI 2.03 to 38.55, P=0.004) compared with those who consistently used BGCs. Conclusion: Our study documents the variations in MT techniques, and more specifically, attempts to quantify variations in the Solumbra technique. The impact of these variations on recanalization rates and eventually patient outcomes are unclear, especially given the self-reported outcomes contained in this study.